Nanofluids revisited. (5th August 2016) - Eggers, Jan Rudolf; Kabelac, Stephan
Highlights: Thermophysical properties bring nanofluids into various engineering applications. Quantity of variable parameters hinder comprehensive equations, e.g. for viscosity. Coordinated research can help to overcome debates about thermophysical properties. Missing experience for nanofluids in large scale plants. Lack of studies about high pressure/temperature applications and long term behavior. Abstract: In the roughly two decades from the first publication until today, nanofluids have found their way into various research fields. To-date published documents range from basic research to high-tech applications. This contribution aims at outlining current fields of research regarding nanofluid research. These range from fundamental property data studies presented in the first section to a listing of numerous applications of different fields of engineering. It is shown that nanofluid science pushes increasingly into the scientific world providing plenty of new questions and challenges.